ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI SIKLUS PENDAPATAN PADA PT XL AXIATA TBK. - Delphian Ramadhan Imaduddin Aksan (2022)
This research is qualitative research. This research took PT XL Axiata Tbk. as the research sample. This research aims to determine how the accounting information system is applied to the revenue cycle of PT XL Axiata Tbk., and to determine the suitability of the accounting information system of PT XL Axiata Tbk. with the main elements of accounting information system. The result of this research indicated that PT XL Axiata Tbk. has implemented an accounting information system in its revenue cycle, and has fulfilled the main elements of accounting information system, which consists: 1) competent human resources, 2) procedures that provide operational activity instructions, 3) transaction evidences, 4) records that are related to company's finance, 5) adequate information technology facilities, and 6) internal control.